Teori filsafat tokoh dan ajarannya - Wahyunani, Aulia Tri (Maliki Interdisciplinary Journal, 2025)
This article explores the philosophical contributions of six major thinkers: Socrates, Plato, Aristotle, Descartes, Kant, and Marx. Each figure introduces a distinct framework for addressing fundamental questions of knowledge, reality, and human values. Socrates advances dialectical reasoning as a method for pursuing ethical clarity through critical dialogue. Plato’s theory of forms presents ideal entities as the true essence behind the physical world. Aristotle constructs a systematic approach to knowledge based on logical reasoning and empirical observation. Descartes, through methodological doubt, establishes reason as the foundation for certainty. Kant synthesizes rationalist and empiricist traditions by emphasizing the mind’s role in structuring experience. Meanwhile, Marx foregrounds historical materialism, asserting that economic and social relations shape consciousness. By weaving together these six perspectives, the article demonstrates that philosophical theories are not merely historical artifacts, but powerful tools for interpreting and engaging with modern societal challenges.